Fibrilación auricular preexcitada en paciente con dos vías accesorias - Moreno-Martínez, Francisco L.; Segura Villalobos, Federico; Gómez Guindal, José A. (CorSalud, 2020)
Fibrilación auricular preexcitada en paciente con dos vías accesorias